Atherogenic Lipoprotein(a) Increases Vascular Glycolysis, Thereby Facilitating Inflammation and Leukocyte Extravasation. Issue 10 (8th May 2020) - Schnitzler, Johan G.; Hoogeveen, Renate M.; Ali, Lubna; Prange, Koen H.M.; Waissi, Farahnaz; van Weeghel, Michel; Bachmann, Julian C.; Versloot, Miranda; Borrelli, Matthew J.; Yeang, Calvin; De Kleijn, Dominique P.V.; Houtkooper, Riekelt H.; et al.
Abstract : Rationale: Patients with elevated levels of lipoprotein(a) [Lp(a)] are hallmarked by increased metabolic activity in the arterial wall on positron emission tomography/computed tomography, indicative of a proinflammatory state. Objective: We hypothesized that Lp(a) induces endothelial cell inflammation by rewiring endothelial metabolism. Methods and Results: We evaluated the impact of Lp(a) on the endothelium and describe that Lp(a), through its oxidized phospholipid content, activates arterial endothelial cells, facilitating increased transendothelial migration of monocytes. Transcriptome analysis of Lp(a)-stimulated human arterial endothelial cells revealed upregulation of inflammatory pathways comprising monocyte adhesion and migration, coinciding with increased 6-phophofructo-2-kinase/fructose-2, 6-biphosphatase (PFKFB)-3–mediated glycolysis. ICAM (intercellular adhesion molecule)-1 and PFKFB3 were also found to be upregulated in carotid plaques of patients with elevated levels of Lp(a). Inhibition of PFKFB3 abolished the inflammatory signature with concomitant attenuation of transendothelial migration. Conclusions: Collectively, our findings show that Lp(a) activates the endothelium by enhancing PFKFB3-mediated glycolysis, leading to a proadhesive state, which can be reversed by inhibition of glycolysis. These findings pave the way for therapeutic agents targeting metabolism aimed at reducing inflammation in patients with cardiovascular disease. Abstract : Supplemental Digital Content is available in the text.